Bio-sanitation treatment using essential oils against E. coli O157:H7 on fresh lettuce. Issue 3 (3rd July 2017) - Mouatcho, Joel Claude; Tzortzakis, Nikolaos; Soundy, Puffy; Sivakumar, Dharini
ABSTRACT: The study was undertaken to develop an effective bio-sanitation treatment using essential oils for the highly perishable leafy vegetable lettuce. The combination of thyme oil and tea tree oil mixed together had a significantly higher total phenolic content as well as higher antioxidant scavenging activity than other single oils or oil mixtures. Lettuce inoculated with Escherichia coli O157:H7 showed significantly reduced population counts in the presence of the sanitation treatment of a combination of thyme + tea tree oil applied by dipping at 0.75% + 0.75% or 1.5% + 1.5% concentrations compared to commercial sodium hypochlorite (200 mg/L NaOCl) washing after 5 days shelf life at 10°C. These results indicate that thyme + tea tree oil dipping treatment could be used to control E. coli O157:H7 contamination in lettuce as an alternative to NaOCl.